Use of metribuzin, associated with different foliar fertilizers, on carrot crops - Soares da Silva, Gustavo; Oliveira Pessoa, Gabriella Daier; Valadão Silva, Daniel; Ramos de Campos, Eduardo; Rodrigues Dos Reis, Marcelo; Da Silva, Antonio Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2019)
1 recurso en línea (páginas 351-358) : ilustraciones color.